2020
DOI: 10.1055/a-1141-3553
|View full text |Cite
|
Sign up to set email alerts
|

Age of First Exposure to Soccer Heading and Sensory Reweighting for Upright Stance

Abstract: US Soccer eliminated soccer heading for youth players ages 10 years and younger and limited soccer heading for children ages 11–13 years. Limited empirical evidence associates soccer heading during early adolescence with medium-to-long-term behavioral deficits. The purpose of this study was to compare sensory reweighting for upright stance between college-aged soccer players who began soccer heading ages 10 years and younger (AFE ≤ 10) and those who began soccer heading after age 10 (AFE > 10). Thirty socce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Four ( 9 11 , 20 ) of the nine studies reported no association between age of first exposure to football and later-in-life brain health problems. Moreover, in all studies of current high school and collegiate athletes, earlier age of first exposure to contact and collision sports has not been associated with worse neurocognitive functioning, subjectively-experienced symptoms, or postural control during preseason baseline testing ( 12 16 , 18 , 19 ), or worse clinical outcome following concussion ( 17 ). Considering the literature more broadly, separate from the issue of age of first exposure to football, results from 7 studies ( 33 38 ) 2 have observed that men who played high school football are not at increased risk for later-in-life neurodegenerative disease ( 36 , 37 ), and they do not report greater mental health problems in their 20s ( 33 , 34 ), during middle age 2 , or during older adulthood ( 35 , 38 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Four ( 9 11 , 20 ) of the nine studies reported no association between age of first exposure to football and later-in-life brain health problems. Moreover, in all studies of current high school and collegiate athletes, earlier age of first exposure to contact and collision sports has not been associated with worse neurocognitive functioning, subjectively-experienced symptoms, or postural control during preseason baseline testing ( 12 16 , 18 , 19 ), or worse clinical outcome following concussion ( 17 ). Considering the literature more broadly, separate from the issue of age of first exposure to football, results from 7 studies ( 33 38 ) 2 have observed that men who played high school football are not at increased risk for later-in-life neurodegenerative disease ( 36 , 37 ), and they do not report greater mental health problems in their 20s ( 33 , 34 ), during middle age 2 , or during older adulthood ( 35 , 38 ).…”
Section: Discussionmentioning
confidence: 96%
“…With time, other research groups have independently conducted 11 studies using diverse samples and methodologies, with none observing an association between earlier age of first exposure to football (or other contact and collision sports) and worse clinical or brain imaging outcomes (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In current high school and collegiate athletes, age of first exposure was not associated with objectively measured neurocognitive functioning, subjectively-experienced symptoms, or postural control across seven highly-powered, observational studies (12-16, 18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…There have been eight published studies on this topic with current high school and collegiate athletes, which inform possible short- to medium-term associations in current athletes. No published studies of current athletes have reported a statistically significant association between playing football (or other contact sports) before the age of 12 and worse functioning ( 84 , 87 , 88 , 90 , 111 , 123 , 124 ), or worse clinical outcome from concussion ( 89 ). These large-scale cross-sectional studies of high school and collegiate athletes have found that earlier AFE to football and other contact sports is not significantly associated with worse objectively measured cognitive functioning ( 84 , 87 , 88 , 90 , 123 ) or greater self-reported physical, cognitive, or emotional symptoms ( 84 , 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to observe whether the findings of prior studies are replicated by future research investigating this association. The best available evidence to date suggests that earlier AFE to contact or collision sports is not associated with worse cognitive functioning or mental health in (i) current high school athletes, (ii) current collegiate athletes ( 84 , 87 , 88 , 90 , 111 , 123 , 124 ), or (iii) middle-aged men who played high school football ( 85 , 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, US Soccer adopted a ban on soccer heading for players aged 10 years old and younger ( 20 ), despite a lack of evidence that initiating heading before age 10 led to poorer outcomes. Caccese et al, used age 10 to retrospectively dichotomize a group of collegiate soccer players into those who began heading the soccer ball at age 10 or younger and those who began heading after age 10 ( 21 ). Caccese et al found no difference in sensory reweighting for upright stance, a marker of sensory reliance for vestibular function, between the soccer players who began heading before or after age 10.…”
Section: Introductionmentioning
confidence: 99%